Vulnerability to Water Shortage Under Current and Future Water Supply‐Demand Conditions Across U.S. River Basins - Hadi Heidari; Mazdak Arabi; Travis Warziniack (Earth's Future, 2021)
Abstract Climate change, population growth, urbanization, and interactions thereof may alter the water supply‐demand balance and lead to shifts in water shortage characteristics at different timescales. This study proposes an approach to improve the vulnerability assessments of U.S. river basins to the shortage at the interannual to decadal timescales by characterizing shifts in intensity, duration, and frequency (IDF) of water shortage events from current (1986–2015) to future (2070–2099) periods. The results indicate that under the driest future climate projection, the frequency and intensity of over‐year (D > 12 months) events at the monthly scale and decadal (D > 10 years) events at the annual scale tend to increase in the Southwest, Southern, middle Great Plain, and Great Lakes regions. Conversely, the frequency of interannual (D < 12 months) events at the monthly scale and annual (D > 1 year) and multi‐year (D > 3 years) events at the annual scale is likely to increase in the West Coast regions. Besides, river basins with a higher rate of aridification are likely to experience more frequent over‐year (D > 12 months) events, while river basins with a decrease in aridification were projected to undergo more frequent interannual (D < 12 months) events due to an increase in the variability of extreme weather anomalies within a year. The findings of this study provide new insights to understand and characterize vulnerability to water shortage under current and future water supply‐demand conditions and can inform the development of effective mitigation and/or adaptation strategies.